Does foot posture differ according to gender and lower extremity muscle strength in pre-adolescent swimmers? - Aykut Özçadırcı; Ferhat Öztürk; Alpan Cinemre; Gizem İrem Kınıklı (Asociación Española de Ciencias del Deporte, 2021)
Abnormal foot adaptations may affect muscle strength and may be associated with injury in athletes. The aim of this study is to investigate whether foot posture differs according to gender and lower limb muscle strength in pre-adolescent swimmers. Pre-adolescent swimmers who were trained at least 8 hours in a week between the ages of 8-12 and who did not have a history of ankle disability and pain were included. The Foot Posture Index (FPI) was used to determine foot posture. The lower limb muscle strength was measured using hand dynamometer. According to FPI total scores, swimmers were divided into two groups as normal footed (n = 36) and pronated (n = 24). Twenty-nine female and 31 male swimmers (mean age F: 11.06±1.53; M: 11.05±1.68 years) participated in the study. Twenty-four subjects had prone foot posture (10 females, 14 males), while 36 subjects had normal foot postures (19 females, 17 males). There was no statistically significant difference between lower extremity muscle strengths (knee flexion-extension, ankle dorsi, and plantar flexion) between swimmers with normal foot posture and swimmers with the prone foot posture (p=0.608, p=0.613, p=0.592, p=0.895 ). In addition, FPI scores were similar by gender (p>0.05). This study revealed that pre-adolescent swimmers with different foot postures had similar lower extremity muscle strength and that foot posture did not differ by gender.